Analysis of the cytotoxic effects of the fruit extract of Crescentia cujete L. (Research, Society and Development, 2022)
Introduction: Over time, treatments with plant species have become more effective for the vast majority of the population, even with a vague collection of scientific research that proves their safety and effectiveness. Among these different species is the arboreal Crescentia cujete L., which is widely distributed in Northeastern Brazil. It is applied with various therapeutic purposes, from antihypertensive, analgesic, antispasmodic and some gynecological disorders. Objective: To analyze the possible cytotoxicity of the hydroalcoholic extract of the fruit. Methodology: The extract was obtained through dynamic maceration in a hydroalcoholic solution. A cytotoxicity analysis was carried out based on the methodologies of osmotic fragility and lethality against Artemia salina L. 45.32%. Conclusion: Therefore, further research aimed at safety and possible applicability of the extract in question is encouraged.